1995
DOI: 10.1007/bf01411436
|View full text |Cite
|
Sign up to set email alerts
|

Coating of intracranial aneurysms: A long-term follow-up study of 34 cases

Abstract: We performed a retrospective follow-up study of 33 patients, with 34 ruptured aneurysms, treated by coating using bio-adhesive polymers. The rebleeding rate after a mean follow-up of 10 years was 18% (6 patients), with 4 cases of early haemorrhage and 2 late rebleedings (late rebleeding rate of 0.7% per year). All rebleedings proved fatal. Coating of the aneurysmal wall provides some protection in patients with "unclippable" aneurysms, but is obviously inferior to clipping, and should be used only in very sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…4,11,12) However, experimental and clinical studies have shown direct vascular and neural toxicity from cyanoacrylate. Cyanoacrylate may cause chronic inflammation, necrosis of the vascular media, and thickening of the arterial wall due to fibrosis in both the media and adventitia, resulting in occlusive arterial lesions.…”
Section: Discussionmentioning
confidence: 99%
“…4,11,12) However, experimental and clinical studies have shown direct vascular and neural toxicity from cyanoacrylate. Cyanoacrylate may cause chronic inflammation, necrosis of the vascular media, and thickening of the arterial wall due to fibrosis in both the media and adventitia, resulting in occlusive arterial lesions.…”
Section: Discussionmentioning
confidence: 99%
“…These medical results raise the possibility of providing critical, additional protection to surgically treated patients (i.e., besides protecting those patients who have been treated by medical means alone). This additional safeguard is needed because surgically treated patients, regardless of technique used (clipping [2], coating [19,31], etc.) along with patients treated by interventional radiologic (endovascular) [4,5] methods, remain at some, as yet not quantified, risk of recurrent hemorrhage in long-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…11 Smith et al (1985) also reported that ethyl 2-cyanoacrylate adhesive could induce acute and chronic granulomatous inflammation of the meninges and evidence of severe vascular damage, including vessel wall necrosis, inflammation, thrombosis, and occasionally hemorrhage in cats. 12 In fact, postoperative complications, including narrowing and occlusion of the parent artery 7,8,11,[13][14][15] and recurrent hemorrhage after total coating 2,7,8,16 have been reported. Thus, the development of a new coating material is urgently required for safe and effective surgery.…”
Section: Introductionmentioning
confidence: 99%